A Pilgrim's Journey—When Parkinson's Disease Comes to an End in Nursing Homes - Lex, Katharina Maria; Larkin, Philip; Osterbrink, Jürgen; Lorenzl, Stefan (Frontiers in Neurology, 2018)
Our interdisciplinary mixed-methods exploratory study was aimed at gaining empirical data on the medical and nursing demands of residents who are in a late stage of Parkinson Disease (PD) and are cared for in residential homes in Salzburg (Austria). In earlier studies it has been concluded that symptom burden of late stage PD patients is similar to or even higher compared with oncological patients. However, although all nine residents who took part in our study had severe limitations in performing their daily activities and experienced enormous restrictions in their mobility, they were quite content with their present living situations and did not show significant symptom burden. From the ethnographic family interviews that we conducted the following features emerged: a strong closeness in the family, an improved quality of life when the patients lived in the nursing home and fears about the future. Therefore, we concluded that living in a nursing home that provides for the needs of these patients is the best option for PD patients in the final stages of their disease as well as for their relatives.